Translating Fredy Neptune: Interview with Thomas Eichhorn. - Petersson, Irmtraud; Eichhorn, Thomas (Australian Literary Studies, 2005)
Interviews German translator Thomas Eichhorn about the translation of the book "Fredy Neptune." Reason for translating the book; Study of the English language by Eichhorn; Impression of the book to Eichhorn.